Menyingkap Tumbuhan Ritual melalui Tradisi : Kajian Etnobotani pada Kirab Jolen di Lumajang, Jawa Timur - Amanda Melia Putri Widianti; Firda Evi Azizah; Nadhia Salma Yusniarni; Salsabila Asshifa Qolbi; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The Kirab Jolen tradition is one of the local wisdom of the Javanese people that utilizes various types of plants, but the local knowledge that accompanies it has the potential to be eroded due to limited scientific documentation. This research aims to document and preserve the local knowledge of the community regarding the use of ritual plants in the Kirab Jolen Tradition. This study uses a qualitative descriptive approach by collecting data through participatory observation, in-depth interviews, and documentation. Informants were determined using purposive techniques followed by snowball sampling, involving village heads, shamans, and community leaders. The data was analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study identified 26 types of plants belonging to 17 families dominated by herbal habitus with the most widely used plant parts in the form of fresh fruits. The ritual plant has a philosophical meaning that is closely related to the value of spirituality and an expression of gratitude to God. Based on the IUCN conservation status, most plants are in the category not evaluated, but the community has implemented local conservation efforts through planting and care in gardens and yards. These findings show that the Kirab Jolen Tradition plays an important role in the preservation of local wisdom, the strengthening of ethnobotanical knowledge, and the sustainability of biological resources.